Reformulasi Wacana Keadilan Sahabat - Adnan Adnan (Diroyah : Jurnal Studi Ilmu Hadis, 2016)
One of hadith discourse is the doctrine of claim that the companions of the Prophet are  the group is considered to know the group's most religious doctrines in the original form. The companions also transmit all riwayah to the next generation. A transmission path can only be accepted if they have the criteria of justice. The problem is, will this criterion of justice was applied to the companions of the Prophet?.This article will to review and discuss back discourse companions justice ('al-Sahabah) is. Rational arguments and historical completing this study to re-open nature of this issue and look at its implications for the study of modern traditions.